Teaching Methods Used by Teachers in Primary Schools Inclusive - M. Yasdar; Suarti Djafar; Elihami Elihami; Faisal Faisal (Universitas Muhammadiyah Enrekang, 2020)
This research aims to ensure that all children with special needs have the same rights to receive an equal education in class with their peers. This research is a descriptive study, which seeks to describe events that exist in the world of education, especially in terms of transferring knowledge to students. The type of research used in this research is qualitative research. The techniques used in data collection are interviews and direct observation in schools. Education and diversity cannot be separated, what needs to be known is how education is able to unite differences by providing good educational equality. Good for normal children and those with special needs. The purpose of education is to encourage good change, both for individuals, groups, and even groups. Inclusive education is child-friendly education, meaning that from any system that services are provided to students who have learning disabilities or special needs learning in ordinary class schools together with their friends.